APLIKASI LAPORAN KEUANGAN TOKO BERKAH AQUATIC BERBASIS WEB - Muhamad Hikayat; Ii Supiandi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
The development and use of information technology has grown rapidly at this time. Especially in store performance efficiency where most of the processes are computerized and certain documents are documented and stored in digital form. One of them is the process for recapitulating the store's financial statements. The results of the business process will become one of the foundations for high-level departments to make decisions. The business process for recapitulating store financial reports that is done manually can certainly cause several problems, including the potential for data loss, or human errors during calculations and daily input documentation and so on. To overcome these problems, of course, a financial application model that focuses on the processing of financial statements can be used. Based on this, this research will build a web-based financial report application that can include financial reports, processing income and expenditure data. This system is made using CodeIgniter while for system development using the waterfall method. Furthermore, the website model will be built with a front-end and back-end equipped with a data base.